LFA-1 Regulates CD8(+) T Cell Activation via T Cell Receptor-mediated and LFA-1-mediated Erk1/2 Signal Pathways - Li, Dan (American Society for Biochemistry and Molecular Biology, 2009)
LFA-1 regulates T cell activation and signal transduction through the immunological synapse. T cell receptor (TCR) stimulation rapidly activates LFA-1, which provides unique LFA-1-dependent signals to promote T cell activation. However, the detailed molecular pathways that regulate these processes and the precise mechanism by which LFA-1 contributes to TCR activation remain unclear. We found LFA-1 directly participates in Erk1/2 signaling upon TCR stimulation in CD8(+) T cells. The presence of LFA-1, not ligand binding, is required for the TCR-mediated Erk1/2 signal pathway. LFA-1-deficient T cells have defects in sustained Erk1/2 signaling and TCR/CD3 clustering, which subsequently prevents MTOC reorientation, cell cycle progression, and mitosis. LFA-1 regulates the TCR-mediated Erk1/2 signal pathway in the context of immunological synapse for recruitment and amplification of the Erk1/2 signal. In addition, LFA-1 ligation with ICAM-1 generates an additional Erk1/2 signal, which synergizes with the existing TCR-mediated Erk1/2 signal to enhance T cell activation. Thus, LFA-1 contributes to CD8(+) T cell activation through two distinct signal pathways. We demonstrated that the function of LFA-1 is to enhance TCR signaling through the immunological synapse and deliver distinct signals in CD8(+) T cell activation.